Manual Measurement Compared With Ultrasonographically Measured Fetal Liver Length (Medical Forum Monthly, 2024)
Objective: To assess the reliability of sonographic measurement of liver length by comparing the measurement of fetal liver length obtained by ultrasonography with that obtained by manual measurement. Material and Methods: 30 fetuses of 18 to 30 weeks of gestation diagnosed as cases of inevitable abortion were selected at the antenatal clinics. Liver length was measured sonographically and after abortion the fetuses were collected and their livers were dissected out for measurement of liver length. Both the sonographic and manually measured readings of liver length were compared. Results: Insignificant difference was found between the manually measured fetal liver length and that measured sonographically at each gestational week of pregnancy. Conclusion: Sonographically measured fetal liver length is accurate and can be used for monitoring fetal well being.